The Ludic Muse: The Form of Games as Art. Issue 1 (April 2016) - Vella, Daniel
Abstract : Taking as its basis Nancy's essay 'Why Are There Several Arts And Not Just One?', this paper makes a case for understanding games as constituting art works bearing a specifically ludic form. It draws on aesthetic theory and philosophy – particularly Kant, Heidegger, Gadamer, and Nancy – in order to theorise the particular aesthetic potential inherent to this form, and the challenges it poses to existing concepts of art and aesthetic engagement. The paper will argue that the player's relation to a game, in contrast to the aesthetic relation as theorised in post-Kantian aesthetics, invokes an active, purposive disposition – and, moreover, that it is this active, purposive disposition itself that is brought forth into presentation by the ludic work. The conclusion reached is that the ludic aesthetic work establishes a gameworld as a sphere of existential praxis for the player, within which she lives a being-in-the-gameworld, which, in being inscribed into the unity of the game as an object distinct from the player, is itself externalised as an object of her aesthetic contemplation.